For the points A(3,3), B(1,2) and C(8,9)
AB=sqrt((1-3)^2+(2-3)^2)=sqrt(4+1)=sqrt(5)~=2.2
BC=sqrt((8-1)^2+(9-2)^2)=sqrt(7^2+7^2)=sqrt(98)=7sqrt(2)~=9.9
AC=sqrt((3-8)^2+(3-9)^2)=sqrt(25+36)=sqrt(61)~=7.8
The case is schematically represented by the figure below
As the sides of the triangle are 5, 8 and 9:
x+y=7sqrt(2)
x+z=sqrt(61)
y+z=sqrt(5) => z=sqrt(5)-y
-> x+sqrt(5)-y=sqrt(61) => x-y=sqrt(61)-sqrt(5)
Adding the first and last equations
2x=7sqrt(2)+sqrt(61)-sqrt(5) => x=(7sqrt(2))/2+sqrt(61)/2-sqrt(5)~=7.737
Using the Law of Cosines:
(sqrt(5))^2=(7sqrt(2))^2+(sqrt(61))^2-2*7sqrt(2)*sqrt(61)*cos alpha
cos alpha=(98+61-5)/(14*sqrt(122))=154/(14*sqrt(122))=11/sqrt(122)
alpha=5.194^@
In the right triangle with x as cathetus, we can see that
tan (alpha/2)=r/x
r=x*tan (alpha/2)=7.737*tan (5.194^@/2) => r=.351